Reputation in an economic game modulates premotor cortex activity during action observation. (4th August 2016) - Farmer, Harry; Apps, Matthew; Tsakiris, Manos
Abstract: Our interactions with other people – and our processing of their actions – are shaped by their reputation. Research has identified an Action Observation Network (AON) which is engaged when observing other people's actions. Yet, little is known about how the processing of others' actions is influenced by another's reputation. Is the response of the AON modulated by the reputation of the actor? We developed a variant of the ultimatum game in which participants watched either the visible or occluded actions of two 'proposers'. These actions were tied to decisions of how to split a pot of money although the proposers' decisions on each trial were not known to participants when observing the actions. One proposer made fair offers on the majority of trials, establishing a positive reputation, whereas the other made predominantly, unfair offers resulting in a negative reputation. We found significant activations in two regions of the left dorsal premotor cortex (dPMC). The first of these showed a main effect of reputation with greater activation for the negative reputation proposer than the positive reputation proposer. Furthermore individual differences in trust ratings of the two proposers covaried with activation in the right primary motor cortex (M1). The second showed an interaction between visibility and reputation driven by a greater effect of reputation when participants were observing an occluded action. Our findings show that the processing of others' actions in the AON is modulated by an actor's reputation, and suggest a predictive role for the PMC during action observation. Abstract : We investigated how the neural processing of a persons' actions during an economic game is influenced by their reputation. We found significantly greater activation in the left dorsal premotor cortex (dPMC) when participants saw the action of a person with a negative reputation compared to a person with a positive reputation. Our findings show that the processing of observed actions is modulated by an actor's reputation, and suggest a predictive role for the dPMC during action observation.